Effeciency of the Designe of waste water treatment unit of Babil Batteries factory in Baghdad (state Battery manufacturing company) - Kawakib Jaber AL-Hashimi; Aid Khalaf Thamer (College of Pharmacy / Mustansiriyah University, 2011)
Industrial waste water is discharged from various processes in factories using water. Further, the contaminants and Pollutants separated from the water, must be treated and disposed of so that they cannot cause environmental pollution of other obstructions. The flow diagram of waste water treatment of babil Battries factory is shown. This was the most suitable treatment methods involving equipments and chemicals. Physical and chemical. Treatment (included PH adjustment) were the methods used, to remove the Pollutants present in the waste water of Bettries factory in Baghdad Determination of chemical properties of final disposal water has been done, estimation tests show good results for many years.